Chemical control of the cyst nematode, heterodera trifolii in miniature carnation (1991)
One of the diseases recently registered on carnation in Colombia is the cystnematode caused by Heterodera trifolii. An increase of the vascular wilt was observed in some farms affected by the two pathogens. A trial was carried out in a commercial greenhouse with miniature carnation of the variety Red Baron. The fumigants DD memethylisothiocianate, Dazomet and Methamsodium applied to the soil before planting were used alone and in combination with three non fumigant nematicides Aldicarb, Carbofuranand Oxamyl, at three different times for the control of the nematode. The fumigants were more efficient than the non fumigant nematicides for the reduction of the population of the nematode in the soil. The best treatment was DD Methylisothiocianate with a 52% reduction of the viable cysts population and 38% reduction of the larvae population in the soil, a reduction of 15 daysin harvesting time, a 9% increase in yield and 19% increase in net income, as compared with the untreated control. Among the three nonfumigant nematicides, the best treatments were Aldicarb and Carbofuran applied atplanting time. Oxamyl applied 30 days afterplanting showed similar results. The cornbination of the fumigants with the non fumigant nematicides did not improuve the nematode control, yield and quality of the flowers. Combination of the two types of nematicides increased the production costs.